Cuando el periodismo decimonónico se puso a soñar. - Hernando, Bernardino M. (Estudios sobre el Mensaje Periodístico, 2000)
Journalism couldn’t be born until the first technical revolution of the spreading of the literary messages: the printing. Since then, journalism has evolved bound to technique and every technical advance has involved a journalistic advance On the threshold of a new millennium, when computer science means the latest for the present journalism revolution, we look back to find out how Spanish journalists from 19 th. and early 20 th. century 153 Bernardino M. Hernando Cuando el periodismo decimonónico se puso a soñar imagined 21 th. century journalism. The French writer Jules Verne dared to do something more: to envisage 29 th. century journalism. Perhaps so much display of imagination in a work so tied to reality as journalism is leads to new views and concepts. Perhaps everything shades into a melancholic scepticism.